Optimizing the Solvent-to-Coffee Ratio for Caffeine Extraction from Arabica Kintamani Coffee Beans using Ethyl Acetate: A Comprehensive Study - sihombing, rony (Journal of Green Science and Technology, 2024)
This paper studies the best ratio of solvent-to-coffee for getting caffeine from Arabica Kintamani coffee beans. It wants to find the optimal ratio that gives the highest caffeine amount and improves the efficiency and quality of extraction. No previous studies have explored the best ratio of Kintamani Arabica coffee beans to ethyl acetate solvent for extracting caffeine. The paper explains the method used, which has four main steps: preparing materials, extracting and measuring caffeine, and analyzing the results. The paper presents the experimental findings and discusses how different ratios affect caffeine content in Arabica Kintamani coffee beans. It uses statistics to show significant differences between the ratios and compares them using Tukey tests. The paper concludes that the best solvent-to-coffee ratio for maximizing caffeine in ethyl acetate extracts is 1:5, resulting in a concentration of 1930.9 ppm. This ratio gives the best balance between caffeine yield and solvent usage.